Prospects for the use of monoclonal antibodies to interleukin 23 Gusеlkumab in psoriatic arthritis: New data - E. L. Nasonov; T. V. Korotaeva; S. Rodolfi; C. F. Selmi (Научно-практическая ревматология)
Among the pathophysiological mechanisms of immune-mediated inflammatory diseases (IMIDs), specific attention has been paid to the abnormal activation of Th17 type immune response related to the dysregulated synthesis of cytokines forming the interleukin (IL)-23 and IL-17 axis. IL-23 blockade is an innovative approach to the treatment of psoriasis and psoriatic arthritis (PsA). Much of the interest has focused on guselkumab (GUS) (TREMFYA, Janssen, Johnson & Johnson, USA), a fully human IgG λ monoclonal antibody (mAb) targeting the p19 IL-23 subunit and the first-in-class treatment approved for patients with psoriasis and PsA. In patients with psoriasis, GUS is at least as effective as other biologic therapies for PsA and is superior to ustekinumab, an anti-IL-12/IL-23 mAb, and secukinumab, an anti-IL-17 mAb. Compared with TNF-α inhibitors, GUS therapy is less likely to cause infections and does not increase the risk of the reactivation of latent TB infection. The new GRAPPA guidelines (2021) recommend GUS (and other IL-23 inhibitors) for patients with PsA resistant to conventional disease-modifying antirheumatic drugs (DMARDs), who have peripheral arthritis, enthesitis, dactylitis, psoriatic skin and nail lesions. The paper discusses new data on the efficacy of GUS in patients resistant to TNF-α inhibitors, its benefits in patients with axial PsA, and safety during the COVID-19 pandemic.